Analysis of the Operational Efficiency Measurement of Domestic Logistics Enterprises Against the Background of a Low-Carbon Economy: -- Based on Three-stage Data Envelopment Analysis Model - Han, Wenxing (Transactions on Economics, Business and Management Research, 2024)
As an indispensable link between low-carbon economic activities, the green development of logistics enterprises determines their market competitiveness and industry development ability. In this paper, 80 domestic logistics enterprises identified in 2022 are selected as objects, and the three-stage data envelope analysis (DEA) method is used to construct the enterprise operation efficiency evaluation index system with the input-output data of 2017–2021. The results show that the overall operating efficiency of domestic logistics enterprises is not high. In 2017, the comprehensive technical efficiency and pure technical efficiency of effective companies reached their peaks, accounting for 22.5% and 35%, respectively. The scale efficiency of effective companies only accounted for 35%. The company's technology and management caliber are negatively impacted by external environmental conditions. There are redundancies in operating input and unreasonable allocations of operating resources. According to the analysis results, this paper puts forward some improvement suggestions for the sustainable development of domestic logistics enterprises from both the government and enterprises.